HENRY A. KISSINGER’S ARTICLE ON TERRORISM: A CRITICAL ANALYSIS - Mokhamad Toha Rudin (Universitas Gadjah Mada, 2014)
The aim of this study is to conduct a critical analysis of Kissinger’s article “America’s Assignment” on Newsweek 2004, and to elaborate US foreign policy toward Islam world and Terrorism after the end if the Cold War, this article also tries to find the ideology or tradition of American foreign policy reflected in Kissinger’s article “America’s Assignment”, and how is Realism ideology reflected in the article. The study employs library research in which the data gathered from books, journals, magazines, and internet. The study also employs Van Dijk’s critical linguistic model for the critical analysis of Kissinger’s “America’s Assignment”.The result of the study shows that Kissinger’s “America’s Assignment” reflects both